Can new disruption research suggest defenses against threats and opportunities for innovators?. Issue 3 (16th May 2016) - Denning, Stephen
Abstract : Purpose: Under the co-direction of John Hagel, Deloitte's Center for the Edge has been publishing important new studies of disruption with an 'outcome-based approach to disruption.' This research is discovering patterns that may help leaders institute defenses against threats and identify opportunities for innovators Design/methodology/approach: Deloitte research is focusing on patterns of disruption that hit more than one market, but not all markets. It is examining: what are the characteristics of markets that would make them vulnerable to a particular pattern? Findings: After six months of research, Deloitte has identified nine patterns that meet its outcome-based criteria. A number of the patterns are based on creating network effects that grow so quickly they become hard to compete with if the rival firm does not already have an established market position. Another set of the patterns identifies ways to fundamentally transform the value-cost equation, but without network effects. Research limitations/implications: More patterns may be discerned as the research proceeds. Practical implications: For example, if incumbents and innovators just think about driverless cars as the auto industry, they are never going to fully see the disruption that is coming. By contrast, by thinking about it as a mobility ecosystem, then many other key players, risks and opportunities become apparent Originality/value: The patterns identified by Deloitte research may provide leaders with insights into how to defend against specific disruptions and also offer innovators inspiration for new opportunities in established markets and Blue Ocean ventures.